The transcription factor ELF4 alleviates inflammatory bowel disease by activating IL1RN transcription, suppressing inflammatory TH17 cell activity, and inducing macrophage M2 polarization - Cao, Meiwan; Chen, Peiyu; Peng, Baoling; Cheng, Yang; Xie, Jing; Hou, Ziang; Chen, Huan; Ye, Liping; Li, Huiwen; Wang, Hongli; Ren, Lu; Xiong, Liya; et al. (Frontiers in Immunology, 2023)
Background: Inflammatory bowel disease (IBD) is a chronic immune-mediated disorder affecting millions worldwide. Due to the complexity of its pathogenesis, the treatment options for IBD are limited. This study focuses on ELF4, a member of the ETS transcription factor family, as a target to elucidate its role in IBD and investigate its mechanism of action in alleviating IBD symptoms by activating IL1RN transcription to suppress the activity of inflammatory TH17 cells.Methods: Using the GEO database, this study examined LPS-induced intestinal inflammatory genes and their regulation mechanisms. We examined the colon length of LPS-treated mice and derived the Disease Activity Index (DAI). H&E staining, ELISA, and flow cytometry were used to detect mice colon tissue damage, inflammatory factor levels in mouse serum, mouse macrophage types and inflammatory TH17 cell activity. RT-qPCR and Western blot detected ELF4, IL1RN, M1, and M2 polarization markers. In Vitro, using dual-luciferase and ChIP assays, we tested mouse bone marrow-derived macrophages (BMDMs) and mouse intestinal epithelial cells for IL1RN promoter activity and ELF4 enrichment.Results: Bioinformatics showed that LPS-induced colitis animals have reduced ELF4 expression in their colon tissue. In vivo tests confirmed reduced ELF4 expression in mice with LPS-induced colitis. ELF4 overexpression reduced mouse intestinal inflammation. ELF4 activated IL1RN transcription in bioinformatics and in vitro tests. ELF4 promoted IL1RN transcription and macrophage M2 polarization to limit intestinal epithelial cell death and inflammation and reduce mouse intestinal inflammation in vitro. ELF4 also reduced the Th17/Treg ratio by increasing IL1RN transcription. Conclusion: ELF4 activates IL1RN transcription, suppresses inflammatory TH17 cells, and induces macrophage M2 polarization to treat IBD.